PENGARUH PRAKTIK BUANG AIR BESAR SEMBARANGAN DI KELURAHAN BELUM ODF SEKANAK RAYA DAN KELURAHAN ODF PATAM LESTARI KOTA BATAM TAHUN 2023 - Indriyani, Rika; Hengky Oktarizal; Anita Pramawati (Jurnal Kesehatan Ibnu Sina (j-kis), 2025)
Abstrack Open Defecation Free (ODF) is a condition in which every individual in a community refrains from practicing Open Defecation (OD). The behavior of stopping Open Defecation (OD) is accompanied by the utilization of sanitary sanitation facilities, such as proper toilets. The aim of this study is to analyze the influence of several factors on the practice of Open Defecation (OD) in two different neighborhoods with different Open Defecation Free (ODF) statuses in Batam City, namely Sekanak Raya Neighborhood (Not ODF) and Patam Lestari Neighborhood (ODF). The research method employed in this study is observational analysis with a cross-sectional approach, involving a sample of 67 households. Data was collected through observations and interviews. The data analysis was conducted using chi-square statistical tests to obtain the results of univariate and bivariate analyses. The research results, measured using the chi-square test, revealed that the level of knowledge of the household heads had a significant effect on the practice of Open Defecation (p-value = 0.003), while the level of income showed no significant effect (p-value = 0.060). The ownership of a toilet (p-value = 0.001), community attitudes (p-value = 0.001), distance from home to public toilet facilities (p-value = 0.001), family support (p-value = 0.115), and the role of healthcare workers (p-value = 0.000) were also found to have significant effects. In conclusion, factors such as education, income, knowledge, community attitudes, toilet ownership, and distance from home to public toilets have an influence on the practice of Open Defecation (OD) in both neighborhoods. To prevent diseases caused by feces, it is recommended that everyone construct proper toilets in their homes or utilize the facilities provided by the local government to improve the ODF status in Batam City.